An Assessment of Employment in Niger - World Bank (World Bank, Washington, DC, 2021)
Due to frequent domestic and external shocks, Niger is one of the poorest countries in the world. Located in a sub-region repeatedly challenged by security threats such as the Libyan conflict, the Mali crisis and the Boko Haram armed attacks, the Nigerien economy is exposed to severe climate shocks that largely impact the country’s economic performance. Despite going through several episodes of political turbulence, Niger has experienced relative political stability, with beneficial effects for economic growth since 2011. To sum up, Niger is a country that faces the jobs challenges of an agrarian and increasingly resource-based economy, and in which a large part of the population is young, poor and exposed to external and internal shocks. In Niger, most population is poor and lives in rural areas, implying that the jobs with the highest development impact are in agriculture. However, as discussed, jobs per se do not guarantee sufficient income opportunities to escape poverty; as such, increases in productivity are crucial for improving living standards. Moreover, giving the high exposure of poor and rural households to climatic shocks and food insecurity, the new jobs agenda needs to encourage the use of modern and inputs and decrease reliance on rainfall patterns. This book is arranged as follows: 1) Chapter one explains the employment structures in Niger; 2) Chapter two discusses employment dynamics and transitions; 3) Chapter three has the analysis of agricultural employment; 4) Chapter four looks at non-agricultural household enterprises; and 5) Chapter five introduces the youth occupational aspirations.